Evaluasi Kenyamanan Jalur Pejalan Kaki di Jalan Merdeka Kota Lhokseumawe - Al Hafis, R; Hassan, S M; Andriani, D (Cered Indonesia Institute, 2024)
One of the cities in Aceh Province that is famous for its scenic beauty is Lhokseumawe. The pedestrian area along Jalan Merdeka is one of the important components in the city's infrastructure. To improve the comfort and safety of citizens and tourists, the pedestrian path should be evaluated. While strolling along Jalan Merdeka in Lhokseumawe, people often discuss various obstacles that interfere with their comfort. Some of the problems often encountered include other damaged sidewalks, lack of nighttime lighting, and indiscriminate parking of vehicles on the sidewalk. Other issues that need to be addressed are the lack of foot crossing signs and lack of attention from motorists. It is important to remove these issues to ensure the safety and comfort of residents and visitors. The research variable is something that wants to be researched and studied, determining the research variable to get some information related to the research. The determination of variables and indicators in this study is adjusted to the aspects that have been compiled. Here are the research variables that have been compiled to serve as a benchmark in this study. Circulation, Climate, Noise, Aroma / odor, Shape, Security and cleanliness.This quantitative research method. To find out people's opinions about the convenience and comfort of pedestrian paths, this method will involve assessing the physical condition of the pedestrian paths on site, pedestrian traffic flow analysis.After conducting observations, finding problems, and making pedestrian development standards at the research site, out of 100 respondents in zone 1 respondents said 61.3% interpretation of Comfortable criteria, that the condition of pedestrian comfort zone 2 respondents said 59.3% interpretation of Moderately Comfortable criteria, in zone 3 respondents said 61.8% interpretation of Comfortable criteria, the sense of comfort for pedestrians is strongly influenced by the physical condition of the highwayPedestrian Infrastructure Improvement: This will improve accessibility for people with disabilities and people with limited mobility by widening sidewalks and providing special pedestrian ramps and signs. installation of Traffic Signs and Lights: placement of traffic signs and lights in strategic locations to ensure pedestrian safety when crossing the road.